Letter from Carl D. Duncan to Patricia Whiting, April 17, 1966 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan describes a lecture he gave the previous night and asks Whiting if there is anything that he can bring to her mother for her.